Ethiopia : Selected Issues. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues paper examines economic development in Ethiopia during the 1990s. In mid-1992, the government began implementing significant economic reforms aimed at stabilizing the economy and deregulating economic activity. Since that time, substantial progress has been made with respect to both objectives. Policy measures have aimed at correcting price distortions, lifting restrictions on the private sector, deregulating the labor market, reducing macroeconomic imbalances, realigning the exchange rate, and liberalizing the external exchange and trade system. Moreover, the decentralization of the political system and reform of the civil service have been initiated.